Leveraging Virtual Contact and Social Networks to Foster Interethnic Harmony - Abu Siddique; Michael Vlassopoulos; Yves Zenou (The Quarterly Journal of Economics, 2026)
Abstract This article investigates whether virtual contact, initiated through a documentary film, can promote interethnic harmony. We carried out a cluster-randomized field experiment involving over 3,300 households across 121 multiethnic villages in Bangladesh. We find that a documentary film, designed to humanize the ethnic-minority Santals and evoke empathy among the ethnic majority Bengalis, increased the ethnic majority’s prosociality toward minorities, though the strength of the evidence varies by treatment arm and outcome. Using emotion-detecting software to analyze facial expressions during the film viewing suggests that the documentary elicited emotional responses consistent with empathy. We do not find evidence that the intervention reduced the prevalence of negative stereotypes and discriminatory opinions toward minorities. In villages assigned to target network-central people, we find positive behavioral effects on untreated individuals, including Santals, and village-level administrative data suggest a reduction in police complaints in those villages. About five months after the intervention, we conducted a casual-work field experiment involving 720 participants from the main intervention. In this task, pairs of ethnic-majority and minority participants jointly produced paper bags for a local supplier under a piece-rate compensation scheme. We find positive treatment effects on productivity for both ethnic groups, with effects concentrated in villages where network-central people were treated. For the ethnic majority, increased prosociality, and for the ethnic minority, reciprocity or peer pressure may have contributed to increased productivity. Overall, our findings suggest that virtual contact and social networks may help promote harmony in multiethnic communities.